Mental Health and Associated Factors among Bangladeshi Migrants in Thailand: a cross-sectional study - Sharmin Sultana; Ann Jirapongsuwan; Mathuros Tipayamongkholgul (Scientific Reports)
Abstract This cross-sectional study investigated the mental health outcomes and associated factors among Bangladeshi migrants in Thailand. A sample of 360 participants completed questionnaires assessing depressive symptoms, anxiety, and stress using the DASS-21 scale, along with sociodemographic and acculturative factors. Results revealed that 35.8%, 42.2%, and 17.8% of participants experienced symptoms of depression, anxiety, and stress, respectively. Lower education levels were associated with increased risk of all three mental health outcomes. Unexpectedly, assimilation as an acculturation strategy and higher Thai language proficiency were linked to poorer mental health. Experiences of discrimination and low social support significantly increased the likelihood of mental health issues. Difficulty accessing healthcare services was also associated with worse mental health outcomes. These findings highlight the complex interplay between acculturation, social factors, and mental health among migrant populations, emphasizing the need for culturally sensitive mental health services and policies to support Bangladeshi migrants in Thailand.